Pengaruh Pembelajaran Kitab Amśīlatu At-Taşrīfiyyah Terhadap Kemampuan Memahami Perubahan Kosakata Bahasa Arab Santri di Pondok Pesantren Nas'atul Muta'allimin Blumbungan Pamekasan - Abdul Malik Saif Ababil; Ainul Yakin (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2024)
Learning is the process of student interaction with educators and learning resources in a learning environment. The learning in this research focuses on studying the book Amśīlatu At-Taşrīfiyyah in understanding word changes based on wazan. So that it can provide understanding to students when processing and changing Arabic vocabulary. The outline of the study of this book that is taught is taşrīf işṭilāḥī and taşrīf lugawī. This research aims to find out the influence of studying the book Amśīlatu At-Taşrīfiyyah on the ability to change Arabic vocabulary and to describe how much influence learning the book Amśīlatu At-Taşrīfiyyah has on the ability of students to change Arabic vocabulary at the Nas'atul Muta'allimin Islamic Boarding School in Blumbungan Pamekasan. This article used a field research methodology that uses a quantitative approach using correlational data analysis techniques to describe two or more facts and properties of the object under study. The results of this study show that: First, there is no strong and significant correlation between learning the book Amśīlatu At-Taşrīfiyyah and the ability to change Arabic vocabulary. Second, the Pearson product-moment correlation test results using the SPSS application and manual calculation show the Pearson correlation value is (0.025) with a Sig level. (0.897). So, based on the correlational table, the r value (0.025) shows a very weak correlation level. The findings of this research indicate that there is no influence from studying the Amśīlatu At-Taşrīfiyyah book on the students' ability to change Arabic vocabulary at the Nas'atul Muta'allimin Blumbungan Pamekasan Islamic boarding school.